Securing the clicks : network security in the age of social media - Bahadur, Gary; Inasi, Jason; Carvalho, Alex de (New York, NY : McGraw-Hill, 2012)
This timely book on social media security risks offers practical, proven methods for assessing the risks posed to corporate networks and how to develop and implement airtight measures and policies to secure those networks while leveraging interdepartmental collaboration.
Includes bibliographical references and index
IT
Keywords: Computer networks -- Security measures; Social media -- Security measures